Temperature performance of a portable solar greenhouse dryer with various collector design - Nurul Aiman Mhd Safri; Zalita Zainuddin; Mohd Syahriman Mohd Azmi; Ahmad Fudholi; Idris Zulkifle; Mohd Hafidz Ruslan (Penerbit Universiti Kebangsaan Malaysia, 2020)
The two main components of a solar greenhouse drying system are the solar collector and drying chamber. Solar greenhouse utilized thermal energy to increase the temperature in the drying chamber at an optimum rate for drying purposes with the use of solar collectors. In this study the performance of a self-built portable solar greenhouse dryer using different types of solar collectors were evaluated, which are flat plate with insulator, V-groove with insulator, flat plate and V-groove with insulator and flat plate and V-groove without insulator. The experiment was conducted indoor, in the solar simulator laboratory using halogen lamps. Two parameters were varied, which are the mass flow rates at 0.011, 0.021, 0.030, and 0.041 kg/s, and the light intensities at 625, 708, 860, and 988 W/m2 . The collector outlet temperature for every solar collector design was compared to each other. The results showed that for all types of collector, the combination of the maximum solar radiation intensity of 988 W/m2 and the lowest mass flow rate of 0.011 kg/s produced the highest average maximum collector outlet temperature. Whereas, the highest efficiency is at the highest mass flow rate of 0.041 kg/s and the minimum solar radiation intensity of 625 W/m2 . In this study it was found that the solar collector that has the best performance of heat transfer is the combination of flat-plate and V-groove collector with an insulator under the V-groove while the best collector design for drying purpose is the combination of flat-plate and V-groove collector without insulator